Microwave pyrolysis and its applications to the in situ recovery and conversion of oil from tar-rich coal: An overview on fundamentals, methods, and challenges. (November 2021) - Ju, Yang; Zhu, Yan; Zhou, Hongwei; Ge, Shirong; Xie, Heping
Abstract: Efficient, safe, and environmentally friendly methods for the low-carbon utilization of coal are required to exploit this resource as a source of cleaner energy. Tar-rich coal can produce a high volume of oil and is abundant in western China. Currently, tar-rich coal is mostly combusted for power generation, which results in wastage of valuable oil resources and serious environmental pollution. Researchers have focused on achieving zero or near-zero carbon emissions while alleviating damage and pollution to geological formations when mining coal resources. In particular, the use of an intelligent unmanned automatic mining machine (UAMM) integrating microwave pyrolysis technology for the in situ mining and conversion of coal into oil and gas has been proposed. However, to date, studies on the microwave pyrolysis of tar-rich coal for the efficient extraction of oil are lacking. In this study, we outline the state-of-the-art developments in the microwave treatments of coal. The principles and advantages of microwave heating compared with traditional heating methods are discussed. Further, current research and applications of microwave-assisted coal processing are reviewed. We also discuss the challenges and future developments in the field of the microwave-based pyrolysis of coal. This report provides a reference for the application of microwave technology to in situ mining, pyrolysis, and conversion of tar-rich coal into liquid energy resources based on a UAMM. Graphical abstract: Highlights: Microwave-based UAMM for in situ mining and conversion of tar-rich coal is introduced. Microwave radiation assists the conversion of tar-rich coal into oil and gas. Microwave promotes the crushing, flotation, drying, grinding and pyrolysis of coal. Challenges and future developments of microwave-based processes of coal are discussed.